Forms of contention : influence and the African American sonnet tradition - Robbins, Hollis, 1963- (Athens : The University of Georgia Press, 2020)
"Forms of Contention: Influence and the African American Sonnet Tradition tells the story of African American sonnet influence: who wrote sonnets and when, who published sonnets, who praised and who opposed the form, who wrote about them critically, how sonnets were included in anthologies, how sonnets have been in and out of fashion, and how sonnet-writers contended with each other. The story of the sonnet's appeal to African American poets from the nineteenth century through the tumultuous twentieth and into the twenty-first, even as sonnet writing remained a vexed pursuit for black poets, for black poetry anthologizers, for Black Arts advocates, and for Black Studies academics, is rich and surprising. Scholarship on black sonnets is only beginning to catch up with the continued output of black sonnets over the past century and a half, particularly in the post-Black Art years. Historically, academic study of African American literature has focused on four concerns: the historical and economic conditions of production and publication of black literature; the political and cultural importance of black literature in America; genres of and trends in black literature; and the nature of the literature as reflective of the black experience. This literary history of African American sonnets engages with these concerns but also opens up a fifth conversation: auxiliary genealogies of influence for black aesthetic production that foreground form and that promote new conversations about form generally: how exactly it enables participation and protest, the overthrow and undermining of aesthetic expectation. Thus, Robbins uses the sonnet as a case study for exploring the broader literary history of African American literature, offering a thorough analysis of the contentious relationship of an old world poetic form to new world poetry"--
Includes bibliographical references (pages 223-243) and index.
Keywords: American poetry -- African American authors -- History and criticism; Sonnets, American -- History and criticism; American poetry -- 19th century -- History and criticism; American poetry -- 20th century -- History and criticism